PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS XI SMA NEGERI 1 SURANENGGALA TAHUN AJARAN 2024/2025 - Aulia, Putri Rizki; Fajri, Khoirul; Unes (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the application of the Problem Based Learning (PBL) model in learning to write procedural texts for class XI students of SMA Negeri 1 Suranenggala and to determine student activities in learning to write procedural texts using the Problem Based Learning (PBL) model. The research method used is Quasi Experimental Designs the research design used is Nonequivalent control group design. Data analysis in this test data taken based on the results of the pretest and posttest tests from 2 groups namely the experiment and control. The average pretest score of the experimental class was 70.20 and increased to 87.08 in the posttest, while in the control class, the average pretest score was 72.16 and increased to 80.41. The results of the two independent sample t-test, namely (independent sample test), obtained t count of 3.555 and t table of 1.679 so t count (3.555) > t table (1.679), which shows that H0 is rejected and H1 is accepted, so there is an influence of learning to write procedural texts using the problem-based learning model. So there is an influence of the Problem Based Learning (PBL) Model in Learning to Write Procedural Texts for Grade XI Students of SMAN 1 Suranenggala in the 2024/2025 Academic Year.